2007
DOI: 10.1016/j.pain.2007.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone and morphine have distinctly different pharmacological profiles: Radioligand binding and behavioural studies in two rat models of neuropathic pain

Abstract: Previously, we reported that oxycodone is a putative kappa-opioid agonist based on studies where intracerebroventricular (i.c.v.) pre-treatment of rats with the kappa-selective opioid antagonist, nor-binaltorphimine (nor-BNI), abolished i.c.v. oxycodone but not morphine antinociception, whereas pretreatment with i.c.v. naloxonazine (mu-selective antagonist) produced the opposite effects. In the present study, we used behavioural experiments in rat models of mechanical and biochemical nerve injury together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
137
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 52 publications
11
137
1
2
Order By: Relevance
“…One explanation of this difference is that, in animal studies at least, oxycodone is thought to act as a kappa-receptor agonist (Nielsen et al, 2007) and these receptors may play an important role in the mediation of visceral pain (Staahl et al, 2006).…”
Section: Chaptermentioning
confidence: 99%
“…One explanation of this difference is that, in animal studies at least, oxycodone is thought to act as a kappa-receptor agonist (Nielsen et al, 2007) and these receptors may play an important role in the mediation of visceral pain (Staahl et al, 2006).…”
Section: Chaptermentioning
confidence: 99%
“…Although opioid receptor agonists with highest affinity for the MOP-R, such as morphine and methadone, have been widely used in the clinic for the treatment of pain (Nissen et al, 2001;Peng et al, 2008), preclinical studies have also demonstrated that KOP-R and DOP-R both play roles in analgesia. The administration of opioid agonists acting at the KOP-R (Leighton et al, 1988;Nielsen et al, 2007;Ross & Smith, 1997;Tiseo et al, 1988) and DOP-R (Kamei et al, 1994;Kamei et al, 1997;Scherrer et al, 2004) produce analgesia and anti-allodynia in rats and mice. Furthermore, co-administration of morphine with a KOP-R or a DOP-R agonist results in enhanced analgesia (Ross et al, 2000;Suzuki et al, 1995).…”
Section: Pain Perceptionmentioning
confidence: 99%
“…Eksperimentelle dyrestudier har gitt opphav til spekulasjoner om at oksykodon og morfin har ulike virkningsmekanismer, og at oksykodon skulle vaere bedre egnet enn morfin i behandlingen av nevropatisk smerte (18). Imidlertid er det stor forskjell på eksperimentelle smertemodeller med gnagere og pasienter med nevropatisk smerte.…”
Section: Dyrestudier Og Eksperimentelle Humane Studierunclassified